Tinjauan Hukum Islam Terhadap Prosesi Mangngesse’ dalam Tradisi Masyarakat Pattae’ di Desa Batetangnga Kecamatan Binuang - Alkadri, Nurmadiah; Nuzha; Noercholis Rafid (QISTHOSIA : Jurnal Syariah dan Hukum, 2024)
This research discusses 1) Procession Mangngesse’ on the traditions of the Pattae' community in Batetangnga Village 2) Review of Islamic Law regarding Processions Mangngesse’ in the traditions of the Pattae' community in Batetangnga Village. This type of research is qualitative research with a focus on field studies (field research). The approach method used is a sociological approach and a normative theological approach (syar'i). Data was collected using observation, interviews and analysis methods. The data that has been collected is then analyzed qualitatively, namely by reducing the data, presenting the data, then connecting theories related to the problem and drawing conclusions to determine the results. The research results show that Procession mangngesse’ in the community tradition pattae' is considered as thanksgiving, tolak bala, and a prayer for safety. Procession mangngesse’ In community tradition, pattae' has religious and ritual value, which brings together Islam and local culture.  Judging from a review of Islamic law regarding processions mangngesse’ it is permissible to do it or the law is Mubah, meaning it is permissible during the procession mangngesse’ is still in line with Islamic teachings and does not deviate from Islamic teachings. Procession mangngesse’ can be done and defended in society. Procession mangngesse’ in line with ‘urf, the rules of Al-‘Adatu Muha}kkamah and Maq>as}id Shariah. The process mangngesse’ contains Islamic values ​​which are expressed in the procession which has symbolic prayers, and the nuances of Islam are felt strongly in its presence fuck me and barazanji.